The bases for lubricating materials synthesized by technologies of thermoplastic waste recycling - Мандзюк, И.; Присяжная, К. (Problems of Tribology, 2016)
It was offered an effective method of estimating oxidation susceptibility of fats and lubricants with the use of the results of rheometric investigations of changes in effective viscosity with a rotational viscometer. A mixture of amine and phenolic high-molecular compounds should be considered as the most effective antioxidant for natural fats with a glance of features of chemical processes accompanying their oxidation.